(untitled) (Biological Sciences - PJSIR, 1995)
Curative effects of garlic were established in a chicken model of atherosclerosis. Atherosclerosis was produced in chickens by feeding them cholesterol-enriched feed for a period of 12 weeks and later administered twice weekly alongwith garlic for another 12weeks. At the end of 24 weeks, the animals were sacrificed and their dorsal aortae were removed to examine the atherosclerotic lesions. The results of studies on blood showed that garlic administration leads to significant decrease in plasma levels oftriglycerides, total cholesterol and LDL( +VLDL)-cholesterol. The aortic dam- age was also significantly lower in the garlic-administered group as compared to the model group fed on cholesterol- enriched feed alone. Tnaddition, aggregation studies showed a marked inhibitory effect of the aqueous extract of garlic on platelet aggregation In vitro. Thus, it may be inferred that administration of garlic provides a significant protection against hyperlipidemia and possibly thrombus formation and therefore has a potential to protect against cardio-vascu- lar anomalies.